Implementation of zakat, infaq, and sadaqah fund distribution through the Sanggar Genius program at the National Zakat Institution Yatim Mandiri Jember - Lestari, Ira Dwi; Siswanto, Adil (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This study aims to analyze the mechanism of ZIS fund distribution through the Sanggar Genius program at LAZNAS Yatim Mandiri Jember and assess the impact of ZIS fund distribution in the implementation of the Sanggar Genius program at Laznas Yatim Mandiri Jember. Method: This study uses a descriptive qualitative method with a purposive approach, namely by selecting informants based on certain criteria. A total of 9 informants were selected, including the Head of the Yatim Mandiri Branch, Yatim Mandiri Program Staff, 5 guidance counselors, and 2 beneficiaries. Data collection techniques were carried out through direct observation in the field, interviews with relevant informants, and collection of relevant documents. Practical Applications: The National Zakat Agency Yatim Mandiri, through the Sanggar Genius program, seeks to improve access to education for orphans and poor families through free tutoring outside of school hours. This program is a form of ZIS fund distribution that focuses on tutoring, character building, and scholarships. Its implementation includes needs surveys, coordination with villages, recruitment of local teachers, and distribution of funds for teacher salaries, learning facilities, and social assistance. Conclusion: The results of this study show that the process of distributing zakat, infaq, and sadaqah (ZIS) funds through the Sanggar Genius Program by LAZNAS Yatim Mandiri Jember Branch has been carried out in a systematic and structured manner, and refers to the principles of Islamic law and applicable regulations, particularly Law Number 23 of 2011 concerning zakat management. The impacts include an increase in the number of Sanggar Genius centers, academic and character development among students, and alleviating the economic burden on parents through free education and intensive mentoring.